Given that x + x 1 = 1 , evaluate the value of x 2 0 + x 2 0 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Solution:
x + 1/ x = 1 --> x 2 + 1 / ( x 2 = − 1
x 4 + 1 / ( x 4 = ( − 1 ) 2 − ( 2 ) = − 1
x 8 + 1 / ( x 8 = ( − 1 ) 2 − ( 2 ) = − 1
x 1 6 + 1 / ( x 1 6 = ( − 1 ) 2 − ( 2 ) = − 1
x 2 0 + 1 / ( x 2 0 = ( x 1 6 + 1 / ( x 1 6 ) ∗ ( x 4 + 1 / ( x 4 ) − ( x 1 2 + 1 / ( x 1 2 )
= ( x 1 6 + 1 / ( x 1 6 ) ∗ ( x 4 + 1 / ( x 4 ) − ( x 8 + 1 / ( x 8 ) ( x 4 + 1 / ( x 4 ) − ( x 4 + 1 / ( x 4 )
= ( − 1 ) ∗ ( − 1 ) − ( − 1 ) ∗ ( − 1 ) − ( − 1 )
( N o t e : Pls. use C O M M O N S E N S E . Use PEMDAS Ofcourse.. You know that i'm only a starter at L a T e X . I h o p e all understand.. : )
= 1 − [ 1 + 1 ]
= 1 − 2
= − 1 ( a n s )
Is it ok now Sir Calvin Lin ? :)
Problem Loading...
Note Loading...
Set Loading...
As x^2 - x + 1 = 0; x^2 = x - 1; x^3 = x^2 - x; Using first equation, x^3 = -1, which when plugged in simplifies the question to finding x^2 + {1/x^2}.